Utilisation of far infrared-emitting garments for optimising performance and recovery in sport: Real potential or new fad? A systematic review - Bontemps, B.; Gruet, M.; Vercruyssen, F.; Louis, J. (PLOS ONE, 2021)
Background: Thanks to the specific materials they embed, far infrared (FIR)-emitting garments can interact with the body`s physiological functions. Such effects have been sought in medicine and physiotherapy for a long time for the treatment/relief of a variety of pathologies and disabling conditions. Recently, FIR-emitting garments have been introduced in the sporting domain under the influence of manufacturers seeing here a new opportunity to support physical performance in athletes, though this is not clearly established. To fill this gap, in this systematic review, we summarize the scientific evidence on the use of FIR-emitting garments in sport and provide directions for future research by shedding light on current scientific limitations. Method: Five scientific databases (PubMed, Cochrane, ScienceDirect, Scopus and SPORTDiscus) were searched by two independent reviewers. Studies investigating the effects of FIR-emitting garments on at least one physiological outcome related to exercise performance and/or recovery in humans were selected. The methodological quality of retained studies was assessed using the Physiotherapy Evidence Database (PEDro) scale. Results and discussion: Eleven studies met the inclusion criteria and were included in the systematic review. Studies investigating similar outcomes related to exercise performance or recovery were scarce and results inconclusive, which prevents from drawing firm conclusion about the utilisation of FIR-emitting garments in athletes. However, these early results show that FIR-emitting garments may be of interest for exercise performance and recovery, mainly through their effects on the body`s thermoregulation and haemodynamic function. The summary provided in this review can be used to inform the design of future studies. (PROSPERO registration number: CRD42021238029).